2019
DOI: 10.1038/s41439-018-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel neuroblastoma amplified sequence (NBAS) mutations in a Japanese boy with fever-triggered recurrent acute liver failure

Abstract: Biallelic mutations in the neuroblastoma amplified sequence (NBAS) gene have been reported to cause two different clinical spectra: short stature with optic nerve atrophy and Pelger-Huët anomaly (SOPH) syndrome and infantile liver failure syndrome 2 (ILFS2). Here, we describe a case of a 3-year-old Japanese boy who presented with fever-triggered recurrent acute liver failure (ALF). The clinical characteristics were considerable elevation of liver enzymes, severe coagulopathy, and acute renal failure. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
See 1 more Smart Citation
“…Progressive reduction in NK cells numbers has been described by Garcia Segarra et al (15) and then by Ricci et al (10). As Figure 2 demonstrates, the patients who had immunodeficiency and bone disease had mutations distributed along the gene, with no particular domain predominance (10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(27)(28)(29)(30)(31)(32)(33)(34)(35), current study).…”
Section: Literature Reviewsupporting
confidence: 72%
“…mortality. Although some degree of liver disease has been associated with most NBAS variants, the mutations associated with severe liver phenotype were either loss-offunction or missense mutations predominantly located in the N-terminal and in the middle part of the NBAS gene (c.409C>T identified in 5 patients: c.680A>C;1749G>A, c.809G>C;2926del, c.1018G>C;2674G>T, c.2819A>C, and c.2819A>C) (15,18,(27)(28)(29)(30)(31).…”
Section: Literature Reviewmentioning
confidence: 99%
“…NBAS mutations have also been identified in SOPH syndrome patients without liver failure [4]. An increasing number of studies have indicated that diseases based on NBAS mutations have a broad phenotypic spectrum, ranging from isolated recurrent ILFS2 to a multi-systemic disease manifesting as short stature, skeletal dysplasia, dysmorphism and optic atrophy with or without liver failure [4][5][6][7][8][9][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the mutations within the NBAS were reported to be the cause of short stature, optic atrophy and Pelger-Huët anomaly of granulocytes (SOPH) syndrome in an isolated Russian yakut population [4]. Increasing research has reported that the phenotype spectrum of NBAS mutations ranges from isolated ILFS2 to a multi-systemic disease including short stature, skeletal dysplasia and optic atrophy [5][6][7][8]. Early administration of antipyretic and support therapy can effectively ameliorate the course of ILFS2 due to NBAS mutations, improving the prognosis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We systematically reviewed the liver pathologies of all patients with NBAS deficiency (previously reported patients 6,16,17,22,26,[30][31][32][33][34] and patients from our cohort). In total, 23 ALF and two non-ALF patients were enrolled.…”
mentioning
confidence: 99%